2015
DOI: 10.1586/17474124.2015.1083856
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the development of portal vein thrombosis in cirrhosis patients

Abstract: The prognostic impact of portal vein thrombosis (PVT) in liver cirrhosis remains controversial among studies, primarily because the risk stratification of PVT is often lacking. A definition of clinically significant PVT should be proposed and actively improved. Moreover, the risk factors for the development of PVT in liver cirrhosis should be fully recognized to screen and identify high-risk patients. Currently, well-recognized risk factors include a reduced portal vein flow velocity, a worse liver function, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 85 publications
1
20
0
Order By: Relevance
“…Chronic liver disease, especially liver cirrhosis, is one of the most common causes of portal vein thrombosis (PVT) [1, 2]. Once chronic liver diseases are diagnosed in patients with PVT, further screening for other thrombotic risk factors is often neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic liver disease, especially liver cirrhosis, is one of the most common causes of portal vein thrombosis (PVT) [1, 2]. Once chronic liver diseases are diagnosed in patients with PVT, further screening for other thrombotic risk factors is often neglected.…”
Section: Introductionmentioning
confidence: 99%
“…It was believed that the disorders in the synthesis of coagulation factors in cirrhotic patients would increase the risk of bleeding, which, however, is contradictory to non-malignant PVT in patients with cirrhosis. Some recent studies (12)(13)(14)have suggested that PVT in cirrhotic patients results from a variety of factors including the decreased portal vein ow velocities, portal vein lymphangitis, and portal brosis. It may also be because that the poor liver function in cirrhotic patients disrupts the balance between pro-and anti-coagulation factors.…”
Section: Discussionmentioning
confidence: 99%
“…Related to the patient population screened for this study (151 potential liver recipients), this corresponds to an incidence of 0.7% antiphospholipid antibodies, 6.6% for increased homocysteine, 7.9% for Factor V Leiden mutation, 11.3% for decreased protein S, 25.8% for decreased protein C, 24.5% for decreased anti-thrombin, and 25.2% for increased lupus anticoagulant. This high incidence of risk factors for thrombosis - in particular the high incidence of positive lupus anticoagulant testing - is an important finding and should lead to further studies in cooperation with other centers in Egypt and overseas to investigate whether this is a local problem or represents a general issue in patients on a liver transplant waiting list [21,22,23,24,25,26]. This would provide important information for developing a protocol for perioperative hemostasis management for recipients in this part of the world, which might be different from other protocols used in overseas centers.…”
Section: Discussionmentioning
confidence: 99%